2006
DOI: 10.1007/s10571-006-9006-3
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Extraneuronal Changes of Immunofluorescence Staining for TNF- and TNFR1 in the Dorsal Root Ganglia of Rat Peripheral Neuropathic Pain Models

Abstract: 1. Several lines of evidence suggest that cytokines and their receptors are initiators of changes in the activity of dorsal root ganglia (DRG) neurons, but their cellular distribution is still very limited or controversial. Therefore, the goal of present study was to investigate immunohistochemical distribution of TNF-alpha and TNF receptor-1 (TNFR1) proteins in the rat DRG following three types of nerve injury. 2. The unilateral sciatic and spinal nerve ligation as well as the sciatic nerve transection were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 45 publications
4
74
0
1
Order By: Relevance
“…These findings implicate that CXCL12/CXCR4 axis might contribute to the pathogenesis of these complications of peripheral neuropathy. Previously, it was found that unilateral nerve injury excited neurons, activated satellite glia, and initiated macrophage invasion at both ipsilateral and contralateral DRG (Dubový et al, 2006(Dubový et al, , 2007, but the mechanisms underlying these phenomena remain unclear. Recently, it was shown that chronic constriction injury (CCI) operation induced chronic pain, which was associated with the increased expression of CXCR4 in neuron and satellite glia in bilateral lumbar and cervical DRG (Dubovy et al, 2010).…”
Section: Cxcl12/cxcr4 Axis and Sciatic Nerve Injurymentioning
confidence: 99%
“…These findings implicate that CXCL12/CXCR4 axis might contribute to the pathogenesis of these complications of peripheral neuropathy. Previously, it was found that unilateral nerve injury excited neurons, activated satellite glia, and initiated macrophage invasion at both ipsilateral and contralateral DRG (Dubový et al, 2006(Dubový et al, , 2007, but the mechanisms underlying these phenomena remain unclear. Recently, it was shown that chronic constriction injury (CCI) operation induced chronic pain, which was associated with the increased expression of CXCR4 in neuron and satellite glia in bilateral lumbar and cervical DRG (Dubovy et al, 2010).…”
Section: Cxcl12/cxcr4 Axis and Sciatic Nerve Injurymentioning
confidence: 99%
“…Following nerve injury there is an invasion of immune cells into the nervous system that is promoted largely by the Wallerian degeneration of the injured nerve as well as by damage of the tissue surrounding the nerve (Chung et al, 2007;Dubovy et al, 2007;Hu and McLachlan, 2002). The immune cells alter the neuronal environment in part by changing the level of various cytokines/chemokines produced by the immune cells and by the neurons and glial cells in response to those released by the immune cells (Austin and MoalemTaylor; Brazda et al, 2009;Dubovy et al, 2006;Dubovy et al, 2010a;Dubovy et al, 2010b). Since some of the immune mediators have been shown to contribute to neuropathic pain by altering the excitability of both primary and secondary sensory neurons one approach that has been investigated to treat/prevent chronic pain is to pharmacologically alter their production.…”
Section: Peripheral Nerve Injury Alters the Dorsal Root Ganglia Envirmentioning
confidence: 99%
“…In addition to the modulation of Kir4.1 expression on SGCs, we could not exclude that a direct action of TNF in the cell body of primary nociceptive neurons might mediate the genesis of herpetic pain. For instance, there are studies showing that TNF is able to sensitize directly the primary sensory nociceptive neurons in vitro (Ohtori et al, 2004;Dubový et al, 2006;Schäfers et al, 2008;Jancálek et al, 2010). TNFR1 is also upregulated in sensory neurons in models of neuropathic and inflammatory pain (Ohtori et al, 2004;Inglis et al, 2005;Dubový et al, 2006;Jancálek et al, 2010).…”
Section: Unexpectedly Tnfr1mentioning
confidence: 99%
“…For instance, there are studies showing that TNF is able to sensitize directly the primary sensory nociceptive neurons in vitro (Ohtori et al, 2004;Dubový et al, 2006;Schäfers et al, 2008;Jancálek et al, 2010). TNFR1 is also upregulated in sensory neurons in models of neuropathic and inflammatory pain (Ohtori et al, 2004;Inglis et al, 2005;Dubový et al, 2006;Jancálek et al, 2010). The generation of specific TNFR1-deficient conditional mice in primary sensory neurons will unravel this issue.…”
Section: Unexpectedly Tnfr1mentioning
confidence: 99%